Renal artery repair with kidney autotransplantation for renal artery aneurysms - Ramouz, Ali; Hafezi, Mohammadreza; Ali-Hasan-Al-Saegh, Sadeq; Shafiei, Saeed; Abbasi Dezfouli, Sepehr; Probst, Pascal; Demirel, Serdar; Böckler, Dittmar; Mehrabi, Arianeb (European journal of vascular and endovascular surgery, 2022)
Objective - Kidney autotransplantation (ATx) is a treatment option for distal renal artery aneurysm (RAA). This systematic review evaluated the indications, treatment strategy, and outcome of kidney ATx to verify the value of this procedure in treating RAA. - Data Sources - PubMed, Embase, and Web of Science. - Review Methods - All study types were included, except study protocols and animal studies, without time or language restrictions. Data sources were reviewed until April 2021 to identify relevant articles evaluating operating time, cold and warm ischaemia time, total complications, length of hospital stay, and mortality rate in patients with RAA receiving kidney ATx. - Results - The literature search retrieved 644 articles. Of these, 55 clinical studies (including 37 case reports and 18 case series) investigating 199 patients were eligible for inclusion. Endovascular treatment had failed in 17% of 70 patients with RAA. Heterotopic kidney ATx was performed in 81% of patients, and 19% received orthotopic kidney ATx. Unplanned nephrectomy was reported in only one patient (0.1%). Post-operative complications were reported in 6.9% of patients, including urinary tract infection (2.0%), wound infection (1.3%), acute renal insufficiency (0.6%), graft thrombosis (0.6%), kidney hypoperfusion (0.6%), haematoma (0.6%), lymphocoele (0.6%), pseudoaneurysm (0.6%), and arterial occlusion (0.6%). None of the patients died peri-operatively, and organ loss was reported in only one patient (0.05%). No further organ loss or death was reported during follow up (median follow up duration 12 months). - Conclusion - In patients with distal perihilar RAA, surgical repair with kidney ATx appears to be a suitable alternative when endovascular approaches are not appropriate. In these cases, kidney ATx saves the kidney and provides good clinical outcomes. However, these findings should be interpreted with caution, considering the lack of data regarding the adverse events, potential for favourable publication bias among included studies, and the absence of consecutive series and prospective trials.
Available online 10 March 2022
Gesehen am 01.07.2022